2020
DOI: 10.1016/j.isci.2020.100946
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Multi-site Genomic Editing of Pseudomonas putida through Thermoinducible ssDNA Recombineering

Abstract: Application of single-stranded DNA recombineering for genome editing of species other than enterobacteria is limited by the efficiency of the recombinase and the action of endogenous mismatch repair (MMR) systems. In this work we have set up a genetic system for entering multiple changes in the chromosome of the biotechnologically relevant strain EM42 of Pseudomononas putida. To this end high-level heat-inducible co-transcription of the rec2 recombinase and P. putida's allele mutL E36KPP was designed under the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…Similar fold repression of targeted proteins by CRISPRi/dCas9 was recently reported 38 , suggestive of a limitation for existing CRISPR systems in P. putida . The plasmid-based CRISPRi system retained stable phenotype for 6 days, but can be further stabilized using genomic integration of the dCpf1/CRISPRi system or by developing multiplex gene deletion strategies 54 , 55 . Directly targeting proteins for degradation in a multiplex format 56 could eventually be applied to prokaryotes 57 and would sidestep the reliance on variable protein turnover kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar fold repression of targeted proteins by CRISPRi/dCas9 was recently reported 38 , suggestive of a limitation for existing CRISPR systems in P. putida . The plasmid-based CRISPRi system retained stable phenotype for 6 days, but can be further stabilized using genomic integration of the dCpf1/CRISPRi system or by developing multiplex gene deletion strategies 54 , 55 . Directly targeting proteins for degradation in a multiplex format 56 could eventually be applied to prokaryotes 57 and would sidestep the reliance on variable protein turnover kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…2. It has been shown that poor ssDNA uptake hampers the efficiency and multiplexing of recombineering-based techniques like MAGE and DIvERGE in P. putida 21 , L. lactis 22 , and M. smegmatis 23 . Optimization of transformation methods is therefore essential.…”
Section: Missing Devices In the Engineering Toolbox Of Non-model Bactmentioning
confidence: 99%
“…Superior ssDNA recombinases have been identified from prophages for P. putida 89 , K. pneumoniae 89 , B. subtilis 154 , L. lactis 22 , and M. smegmatis 153 , but the recombination frequencies remain well below those reported for E. coli , which in turn limits large-scale, multiplexed engineering efforts. Moreover, the use of alternative recombinases requires time-consuming optimization of recombinase expression levels and oligonucleotide design 21 , 89 , 153 , 154 . 4.…”
Section: Missing Devices In the Engineering Toolbox Of Non-model Bactmentioning
confidence: 99%
See 2 more Smart Citations